KADAR TOTAL FLAVONOID DAN UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN GAHARU (Gyrinops versteegii) - Parwata, I. M. O. A.; Kusuma, I N. A.; Dewi, I. G. A. K. S. P. (Jurnal Kimia (Journal of Chemistry), 2022)
Natural antioxidants derived from the group of flavonoid compounds in plants as alternative antioxidants continue to increase their use, development and research. One of them is agarwood ( Gyrinops versteegii) that is widely used as a traditional medicine, where the substances that are thought to be responsible are flavonoid compounds. This study was conducted to determine the total flavonoid content in the ethyl acetate fraction of agarwood leaves and their antioxidant activities. The total flavonoid content was determined based on the absorbance value measured at a wavelength of 415 nm by using UV-Vis spectroftometer, with a quercetin as standard for comparison. The antioxidant activity test of the ethylacetate fraction of Gyrinops versteegii leaves was carried out by measuring the scavenging activity of DPPH radical (1,1-diphenyl-2-picrylhydrazyl) using UV-Vis spectrophotometer at a wavelength of 517 nm. A total of 100 grams of dry agarwood leaf powder were macerated with 2L aqua DM (70 o C – 80 o C) and 400 mL of concentrated extract was obtained. The next partition with ethyl acetate, chloroform and hexane produced concentrated fractions of 8.27 grams, 4.05 grams and 5.58 grams, respectively. Qualitative analysis using phytochemical tests showed that the ethyl acetate fraction positively contained flavonoids with the highest intensity of color change. The results showed that the total flavonoid content obtained from the ethyl acetate fraction of agarwood leaves was 840.12 mg QE/100 grams and IC 50 60.40 ppm. This value indicated that the ethyl acetate fraction of Gyrinops versteegii leaves had high levels of total flavonoids and strong antioxidant activity. Keywords: agarwood ( Gyrinops versteegi) leaves, antioxidants, DPPH, IC 50 .